Benefits of treatment with rasagiline for fatigue symptoms in patients with early Parkinson's disease. (21st June 2013) - Stocchi, F.; ,
<x xml:space="preserve">Abstract</x> Background and purpose Fatigue is a common symptom of Parkinson's disease (PD), often considered by patients as one of the most disabling PD symptoms with significant impact on quality of life. Our aim was to assess the benefits of rasagiline treatment on fatigue in early PD patients. Methods In this sub‐study of ADAGIO (N Engl J Med 2009; 361: 1268), 1105 untreated PD patients were randomized to receive rasagiline 1 mg/day (n = 270) or 2 mg/day (n = 277) or placebo (n = 558) for 36 weeks. The 16‐item Parkinson Fatigue Scale (PFS) was assessed at baseline and at week 36/early withdrawal visit. Changes from baseline to last observed visit for each rasagiline group were compared with placebo using ancova. Results Mean baseline PFS score was 2.2 ± 0.9 units. At 36 weeks, patients receiving placebo showed greater progression of symptoms (0.17 units) from baseline in PFS scores compared with the 1 mg/day (0.03 units) and 2 mg/day rasagiline groups (−0.02 units); the difference versus placebo was significant for both rasagiline groups (P < 0.01). Conclusions Symptoms of fatigue can be detected in patients with early PD and progressively worsen over time. Rasagiline was associated with significantly less progression of fatigue compared with placebo over a 9‐month period.